The Impact of Expressive Activities Course on Personal and Professional Growth of University Students - Entisar Smadi (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
The study aims to identify the effect of lectures in the expressive activities course on the levels of personal and professional growth among a sample of students from the Department of Counseling and Mental Health at the World Islamic Science and Education University, Jordan. A scale of personal and professional growth was prepared, in addition to activities to be applied in Expressive Activities course, as tools of the study. The study population consisted of all students of the Department of Counseling who were registered in the second semester of the academic year 2019/2020 and who numbered 562 male and female students. The study sample consisted of 36 male and female students as an experimental group, and 36 male and female students as a control group. The personal growth and the professional growth scale was applied to the members of the two groups. Moreover, the lectures that included expressive activities were given to the members of the experimental group. At the end of the semester, the personal and professional Growth Scale was applied as a post-test. The results showed a statistically significant effect of the lectures on expressive activities in improving the level of personal and professional growth of students. The study recommends designing the lectures on expressive activities in a practical way to achieve personal and professional growth for students studying counseling.